The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-54056-7
|View full text |Cite
|
Sign up to set email alerts
|

Marine fog inputs appear to increase methylmercury bioaccumulation in a coastal terrestrial food web

Abstract: Coastal marine atmospheric fog has recently been implicated as a potential source of ocean-derived monomethylmercury (MMHg) to coastal terrestrial ecosystems through the process of sea-to-land advection of foggy air masses followed by wet deposition. This study examined whether pumas (Puma concolor) in coastal central California, USA, and their associated food web, have elevated concentrations of MMHg, which could be indicative of their habitat being in a region that is regularly inundated with marine fog. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 72 publications
2
23
2
Order By: Relevance
“…1 A). The absolute values of THg in Usnea lichens from the coast in the south of the Russian Far East turned out to be higher than in the Ramalina menziesii lichens (from the same order Lecanorales and the same ecological form as Usnea ) from the coast in California 3 (0.138 ± 0.012 mg kg −1 ). It is possible that such differences are related to species-specific features of their thalli.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…1 A). The absolute values of THg in Usnea lichens from the coast in the south of the Russian Far East turned out to be higher than in the Ramalina menziesii lichens (from the same order Lecanorales and the same ecological form as Usnea ) from the coast in California 3 (0.138 ± 0.012 mg kg −1 ). It is possible that such differences are related to species-specific features of their thalli.…”
Section: Resultsmentioning
confidence: 78%
“…Weiss-Penzias et al 3 do not give the average THg for inland lichens, but they show that the high MMHg content in lichens on the coast is obtained through coastal marine atmospheric fog. We compared our data with those for THg on Bathurst Island 22 , where the spatial pattern in THg enrichment was very similar to that of MMHg, with enrichment highest at coastal sites and decreasing within 10 km, suggesting similar origins of atmospheric THg and MMHg to lichens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other elemental contaminants of California pacific coastal fog were found to be consistent with CFA contamination [52]. Recent investigations of a limited number of species demonstrated that pacific coastal biota had significantly greater mercury content than comparable species from inland areas not exposed to the coastal fog [93]. Although bats were not included in that study, they should be for future investigations.…”
Section: Fig 2 Average Metallic Composition Of Insectivorous Male Bmentioning
confidence: 80%